The indigenous cattle of the British dependent territories in Africa with material on certain other African countries (Her Majesty's Stationery Office, 1957)
Survey report on indigenous cattle in Africa. The document is divided into 5 parts, detailing distinctive types and breeds of indigenous cattle in the region. Classification and groupings of the cattle are based on geographic regions and earlier works by Epstein. The origin and history of African cattle are dealt with in detail in part four. Other topical issues discussed include environmental conditions under which the animals are found, conformation and qualities of the cattle. Detailed information on some selected breeds and their comparative performance to crossbreds, illustrations and references included.